SIMBOL DAN KONSEP RELIGIUSITAS DALAM ROMAN SIDDHARTHA KARYA HERMANN HESSE - Saputri, Anggi Jeny Ramadhani; Haryati, Isti (SUSASTRA: Jurnal Ilmu Susastra dan Budaya, 2023)
This study aims to describe the meaning of symbols and the concept of religiosity contained in the text of the romance Siddhartha by Hermann Hesse with.The source of the data in this study is Hermann Hesse's romance Siddhartha published in 1922. The data were analyzed by qualitative descriptive analysis techniques using a hermeneutical approach. The validity of the data is obtained from validity tests and reliability tests.The results showed that there are two symbols and four concepts of religiosity contained in Hermann Hesse's Siddhartha romance. The symbol found is a symbol of unity and a symbol of immortality. The symbol of unity is indicated by "Om", while the symbol of immortality is indicated by the river and its flow. The concept of religiosity includes ritual involvement, ideological involvement, intellectual involvement, experiential involvement, and consequential involvement.